List of Persons outside the Service who have passed the Interpreters’ Examination (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial telegram on Interpreters examination result
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies